2023
DOI: 10.1021/acsnano.3c00891
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic and Photothermal Therapies: Synergy Opportunities for Nanomedicine

Abstract: Tumoricidal photodynamic (PDT) and photothermal (PTT) therapies harness light to eliminate cancer cells with spatiotemporal precision by either generating reactive oxygen species or increasing temperature. Great strides have been made in understanding biological effects of PDT and PTT at the cellular, vascular and tumor microenvironmental levels, as well as translating both modalities in the clinic. Emerging evidence suggests that PDT and PTT may synergize due to their different mechanisms of action, and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
114
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(116 citation statements)
references
References 236 publications
1
114
0
1
Order By: Relevance
“…278,551 Compared with traditional photosensitizers, such as hematoporphyrin, chlorin, methylene blue, 5-aminoketovaleric acid, and phthalocyanine, 0D CNMs exhibit water solubility, photostability, selectivity, toxicity, biocompatibility, and oxygen production efficiency. 552 In addition, a long-wavelength red or NIR emission and high QY are important for avoiding the interference autobackground fluorescence in biological systems. 283 Photothermal therapy uses materials that exhibit a high photothermal conversion efficiency to kill cancer cells.…”
Section: In Vitro and In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…278,551 Compared with traditional photosensitizers, such as hematoporphyrin, chlorin, methylene blue, 5-aminoketovaleric acid, and phthalocyanine, 0D CNMs exhibit water solubility, photostability, selectivity, toxicity, biocompatibility, and oxygen production efficiency. 552 In addition, a long-wavelength red or NIR emission and high QY are important for avoiding the interference autobackground fluorescence in biological systems. 283 Photothermal therapy uses materials that exhibit a high photothermal conversion efficiency to kill cancer cells.…”
Section: In Vitro and In Vivomentioning
confidence: 99%
“…In PDT, 0D CNMs are usually employed as the photosensitizer, which is regarded as the key aspect of PDT . To function as the photosensitizer, metal-ion-doped 0D CNMs are highly suitable because they can not only emit fluorescence but also function as catalyst to produce O 2 and 1 O 2 by catalyzing endogenous H 2 O 2 inside tumor cells in the acidic tumor microenvironment to overcome hypoxia in solid tumors and promote the efficiency of PDT. , Compared with traditional photosensitizers, such as hematoporphyrin, chlorin, methylene blue, 5-aminoketovaleric acid, and phthalocyanine, 0D CNMs exhibit water solubility, photostability, selectivity, toxicity, biocompatibility, and oxygen production efficiency . In addition, a long-wavelength red or NIR emission and high QY are important for avoiding the interference autobackground fluorescence in biological systems …”
Section: Optical Properties Of 0d Cnmsmentioning
confidence: 99%
“…Photodynamic therapy (PDT) is emerging as an attractive modality for cancer therapy owing to the high spatiotemporal selectivity, minimal invasiveness, and low systemic toxicity. Mitochondria are highly sensitive to reactive oxygen species (ROS), and the mitochondrial apoptosis pathway plays an important role in most antitumor mechanisms. Particularly, accumulating evidence has demonstrated that mitochondria-targeting PDT can activate the cyclic GMP-AMP synthase (cGAS)-stimulator of interferon gene (STING) pathway-based innate immunity by inducing mitochondrial DNA (mtDNA) damage and release. mtDNA contains inflammatory non-methylated CpG sequences, which is similar to bacterial DNA that can activate the cGAS-STING pathway. Thus, efficient mitochondria-specific photosensitizer (PSs) accumulation is highly recommended to improve PDT and PDT-triggered innate immunity.…”
Section: Introductionmentioning
confidence: 99%
“…17 Nanoporous organic polymers (POPs) are a subclass of artificial porous materials widely used in gas separation/ storage, catalysis, energy conversion, etc., due to its simple design, clear composition, and ultrahigh surface area. 18 Compared with other traditional porous materials, POPs feature excellent structural diversity, which is frequently used as a drug-delivery system for biological analysis and disease therapy. 19 In addition, as a new type of multifunctional material, POPs with intrinsic optical−chemical properties could be used as ideal treatment agents achieving synergistic therapy and have brought new development directions to the medical industry.…”
Section: ■ Introductionmentioning
confidence: 99%